2010
DOI: 10.1038/ijo.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Normal mitochondrial function and increased fat oxidation capacity in leg and arm muscles in obese humans

Abstract: Aim/hypothesis: The aim of this study was to investigate mitochondrial function, fibre-type distribution and substrate oxidation during exercise in arm and leg muscles in male postobese (PO), obese (O) and age-and body mass index (BMI)-matched control (C) subjects. The hypothesis of the study was that fat oxidation during exercise might be differentially preserved in leg and arm muscles after weight loss. Methods: Indirect calorimetry was used to calculate fat and carbohydrate oxidation during both progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 59 publications
14
87
0
Order By: Relevance
“…Bogdanis et al [25] have observed that the Fat max in overweight and sedentary men and women have a low exercise intensity (about 50% and 40% VO 2max , respectively). Ara et al [43] have reported that young male obese individuals have higher exercise intensity than normal-weight individuals for the Fat max . In contrast, the present study results show that Fat max and the corresponding exercise intensity are similar in the groups for absolute and relative lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Bogdanis et al [25] have observed that the Fat max in overweight and sedentary men and women have a low exercise intensity (about 50% and 40% VO 2max , respectively). Ara et al [43] have reported that young male obese individuals have higher exercise intensity than normal-weight individuals for the Fat max . In contrast, the present study results show that Fat max and the corresponding exercise intensity are similar in the groups for absolute and relative lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Greater capacity to oxidize fat during exercise in the muscle has been reported in obese compared to lean subjects well matched for physical fitness, showing an association between fat oxidation capacity and body fat mass (Schutz et al 1992;Goodpaster et al 2002;Horowitz and Klein 2000;Ara et al 2011). The higher fat oxidation in obese compared to lean was due to higher oxidation of intramuscular triglycerides since plasma fatty acid oxidation was similar (Goodpaster et al 2002;Horowitz and Klein 2000).…”
Section: Introductionmentioning
confidence: 89%
“…The inclusion criteria for the PO group were: (1) BMI levels lower than 30 kg m −2 like C subjects; (2) weight loss through non-pharmacological or surgical therapies of at least 10 % of their body weight [on average the weight loss was 26 % (range 15-37 %)] and, (3) weight stability at the time of the study (±2 kg for at least 1 month prior to the beginning of the experiments) for all groups. The weight loss of the PO subjects had on average occurred 6 ± 1 years earlier (range 1-10 years) (Ara et al 2011) and the weight loss was achieved by means of a combination of hypo-caloric dieting and increased physical activity and none had undergone bariatric surgery.…”
Section: Methods and Procedures Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008). Several studies show that insulin resistance arises when mitochondrial function is unaffected or even improved , Ara et al 2011, Boudina et al 2012, or conversely that impaired mitochondrial functioning alone does not cause insulin resistance (Wredenberg et al 2006). These latter findings data seem to indicate that, at least in rodents, consumption of high-fat diet is not always accompanied by mitochondrial dysfunction, but rather leads to improved mitochondrial oxidative capacity and/or biogenesis (Gómez-Pérez et al 2012, Wessels et al 2015, even in the presence of IR.…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%